2018
DOI: 10.11606/s1518-8787.2018052000190
|View full text |Cite
|
Sign up to set email alerts
|

Características das mulheres que não consultam com médico: estudo de base populacional

Abstract: OBJECTIVETo analyze the prevalence of not consulting a doctor within a year.METHODSCross-sectional population-based study, including women aged 20–60 years, living in the urban area of São Leopoldo, state of Rio Grande do Sul, in 2015. The association between variables and outcome was assessed using prevalence ratios and 95% confidence intervals (95%CI). The adjusted analysis was performed using Poisson regression with robust variance.RESULTSAmong the 1,127 women participating in the study, 954 (84.6%, 95%CI 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…However, our data highlight the fact that between 40 and 49 years old, the prevalence of multimorbidity was 16.3%, while at 50-59 years, it became 39%. Even considering that women consult the doctor more as they age and are, therefore, more likely to be diagnosed with health problems 31 , it is observed that middle age has a significant impact on the occurrence of multimorbidity, which thus indicates an important avenue for prevention. Although it was not evaluated in our study, the hypothesis that our findings are related to the menopausal status of these women cannot be ruled out, since the post-menopause phase is associated with multimorbidity 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our data highlight the fact that between 40 and 49 years old, the prevalence of multimorbidity was 16.3%, while at 50-59 years, it became 39%. Even considering that women consult the doctor more as they age and are, therefore, more likely to be diagnosed with health problems 31 , it is observed that middle age has a significant impact on the occurrence of multimorbidity, which thus indicates an important avenue for prevention. Although it was not evaluated in our study, the hypothesis that our findings are related to the menopausal status of these women cannot be ruled out, since the post-menopause phase is associated with multimorbidity 16 .…”
Section: Discussionmentioning
confidence: 99%
“…On evaluating social inequality indicators, an association was observed between low-income or lower socioeconomic status and multimorbidity 19,21,44,45,50 However, similar to our findings, data from the PNS 2013 showed that the southern states of Brazil, which are more developed in terms of both income and education, showed an increase in the occurrence of multimorbidity, possibly related to an increase in the life expectancy in these states in comparison with the others states 42 . Additionally, it is known that higher income is associated with greater access to health care services 31 , which may be related to a higher number of diagnoses and, therefore, a higher percentage of multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality control was also performed through the application of a reduced questionnaire, which included variables that were unlikely to have changed in a short time. This step was carried out through telephone contact with a random sample of 10% of the participants included in the study 20–22 …”
Section: Methodsmentioning
confidence: 99%
“…This step was carried out through telephone contact with a random sample of 10% of the participants included in the study. [20][21][22]…”
Section: Larger Studymentioning
confidence: 99%